2000
DOI: 10.1089/end.2000.14.661
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Microwave Thermotherapy: An Alternative to Medical Management in Patients with Benign Prostatic Hyperplasia?

Abstract: Transurethral microwave thermotherapy (TUMT) is being increasingly considered as an alternative to medical management with alpha-blockers or finasteride in patients with lower urinary tract symptoms (LUTS) of benign prostate hyperplasia (BPH). Enduring clinical benefits have been demonstrated after a single 1-hour microwave treatment session under topical anesthesia, and the associated morbidity is low. Optimal results are obtained with the delivery of high thermal doses and accurate targeting of microwave ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The limitations of ·-lytic therapy are its loss of effectiveness in 5.8% of patients and the side effects reported in 13.3-20.4% of cases. The maximum effect of finasteride is modest and it takes some months to manifest itself [22].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of ·-lytic therapy are its loss of effectiveness in 5.8% of patients and the side effects reported in 13.3-20.4% of cases. The maximum effect of finasteride is modest and it takes some months to manifest itself [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the efficacy of HeTUMT in treating BPH [1–3,8–12,16–21], and when compared with a sham procedure [17,21]. The method is thought to decrease subjective complaints by 50% at 6 months after treatment, decrease the PVR by 30–69%, and increase the flow rate by 45–84% [3,8,9,11,12,16,21].…”
Section: Discussionmentioning
confidence: 99%
“…The place of HeTUMT amongst treatment methods for BPH remains to be established, but it is considered to be a serious alternative to pharmacotherapy, with a delayed but more durable effect and a lower failure rate [1,2]. He‐TUMT can be administered as an outpatient procedure, with no need for anaesthesia, and patients at high surgical risk, as assessed by the ASA scale, can be treated safely [3,4].…”
Section: Introductionmentioning
confidence: 99%